Hydrogen peroxide treatment induces the transposition of an insertion sequence in Deinococcus radiopugnans DY59 - Shin, Eunjung; Noh, Hee Seong; Ye, Qianying; Lee, Sung-Jae (Frontiers in Microbiology, 2023)
Deinococcus radiopugnans DY59 (formerly Deinococcus swuensis DY59) is a radiation-resistant bacterium isolated from soil. From the 3.5 Mb genomic DNA sequence of strain DY59 (December 2014), 31 insertion sequence (IS) elements of six IS families including IS1, IS4, IS5, IS66, IS630, and IS701 and five unclassified IS elements were detected. Upon induction of oxidative stress with 80 and 100 mM H2O2, the unique ISs of the IS4 family member were actively translocated into a carotenoid biosynthesis gene phytoene desaturase (QR90_10400), resulting in non-pigment phenotypic selection. Therefore, these active transpositions of a specific IS family member were induced by oxidative stress at 80 and 100 mM H2O2. Furthermore, D. radiopugnans DY59 exhibited extremely higher MIC values against H2O2 treatment. To explain this phenomenon, qRT-PCR was conducted to assess the expression levels of catalase and three LysR family regulators. Our findings indicated that the ISDrpg2 and ISDrpg3 elements of the IS4 family were actively transposed into the phytoene desaturase gene by H2O2 treatment via replicative transposition. However, high H2O2 resistance did not originate from H2O2-induced expression of catalase and LysR family regulators.